Patterns of Literacy and Numeracy Activities in Preschool and Their Relation to Structural Characteristics and Children's Home Activities - Simone Lehrl; Wilfried Smidt; Christiane Grosse; David Richter (Research Papers in Education, 2014)
Early literacy and numeracy activities in family and preschool are considered important for promoting children's early literacy and numeracy skills. However, little research exists, especially in Germany, on the frequency of such activities in different contexts. The current study identified patterns of literacy and numeracy activities in preschools and their relation to structural preschool characteristics and to attributes of the home learning environment. Four hundred twenty-one children attending 89 preschool classes in two German federal states were examined. The results indicate that preschools fall into three different profiles of literacy and numeracy activities: low levels of engagement in both domains, numeracy-oriented engagement and literacy-oriented engagement. Additionally, structural characteristics of the preschools, family literacy and numeracy activities were found to predict children's profile membership. The study's implications for future research and early education are discussed.
Additional information: This is an Author's Accepted Manuscript of an article published in Research Papers in Education 29 (2014), 5, p. 577-597, available online at: http://www.tandfonline.com/10.1080/02671522.2013.792865
Keywords: 330; preschool engagement; literacy; numeracy; home learning environment